New concepts on the constructive sequence and functions of the canals’ network of Chavín de Huántar - Bustamante, Julio (2021)
Using the information made available by the discovery of new canals in the Ceremonial center of Chavin de Huantar the present paper deepens the study of the origins and uses of Chavín’s hydraulic system –mainly to drain rainfall and ritual purposes, as well as a possible water supply– and investigates the influence of this development in later pre-Columbian constructions. Taking into account the latest knowledge of Chavin’s architectural sequence, the paper formulates from a hydraulics viewpoint a proposal for the construction stages of the canal networks and explores the growth of knowledge implied by this process.